ANALISIS PENYELESAIAN SENGKETA DIVESTASI SAHAM ANTARA PEMERINTAH REPUBLIK INDONESIA DENGAN PT. NEWMONT NUSA TENGGARA YANG DIKAITKAN DENGAN PERJANJIAN KONTRAK KARYA - Kartika Cahyaningtyas; Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2024)
This study examines and analyzes the Implementation of the International Arbitration Decision in the share divestment dispute between the Government of the Republic of Indonesia and PT. Newmont Nusa Tenggara. This needs to be studied because of the share divestment dispute between the Government of the Republic of Indonesia and PT. Newmont Nusa Tenggara which is related to the Work Contract Agreement. The method used is normative research with a statutory and case approach. The results of this study are that the Government of the Republic of Indonesia and PT. Newmont Nusa Tenggara also made a Work Contract Agreement in written form. However, over time PT. Newmont Nusa Tenggara committed an act of default in the form of not doing what it promised to do for share divestment. Every company must be able to implement the Company Performance Rating Assessment Program (PROPER), which includes; gold rating, green rating, blue rating, red rating, and red rating. This has the main objective of environmental preservation and management. If the company does not implement the Company Performance Rating Assessment Program (PROPER), then there are sanctions that must be accepted. Keywords: Dispute, Share Divestment, International Arbitration Decision